Validity and reliability testing of home care stroke quality indicators - Nur Chayati; Christantie Effendy; Ismail Setyopranoto (International Journal of Public Health Science (IJPHS), 2021)
It is disconcerting that until today there are no agencies or research to recommend the appropriate indicators of home nursing care of stroke patients according to Indonesian conditions. Hence, this research aimed to verify the validity and reliability of quality indicators of home nursing care for stroke patient that resulted from Delphy process. Confirmatory factor analysis was carried out for validity and reliability testing with data collected from 350 respondents. Based on the value of loading factors, 62 indicators were declared valid and five indicators were invalid. This study successfully proved the validity of 62 indicators of quality home care for stroke patients. Further research is needed to pilot project this indicator in a larger area.